1990
DOI: 10.1161/01.atv.10.6.991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Gla-containing protein from calcified human atherosclerotic plaques.

Abstract: In this article we describe the isolation of a 4-carboxyglutamic acid (Gla)-containing protein from calcified human atherosclerotic plaques. The protein was extracted from pulverized calcified plaques by demineralization with ethylenediaminetetraacetate and was subsequently purified by anion-exchange fast protein and highperformance liquid chromatography by using ion-exchange and gel-filtration columns. The protein was designated as plaque Gla protein (PGP) and has an apparent mass of 23 kD as estimated from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 17 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…6,23,25,26,60 Although osteocalcin has been extracted from atherosclerotic plaques, 31,32 we did not detect it associated with any cell types in any of the atheromas examined. Because in this work we have shown that osteocalcin colocalized with fibrin II/calcium deposits, it might be derived from plasma and/or platelets.…”
Section: Role Of Bone-related Noncollagenous Proteins In Atherosclermentioning
confidence: 55%
“…6,23,25,26,60 Although osteocalcin has been extracted from atherosclerotic plaques, 31,32 we did not detect it associated with any cell types in any of the atheromas examined. Because in this work we have shown that osteocalcin colocalized with fibrin II/calcium deposits, it might be derived from plasma and/or platelets.…”
Section: Role Of Bone-related Noncollagenous Proteins In Atherosclermentioning
confidence: 55%
“…Osteocalcin, a protein containing Gla-residues (28) has been extracted from human calcified arterial plaques (29). An additional calcium-binding Gla-containing protein named plaque Gla protein (PGP) was isolated from human calcified plaque (30). Osteocalcin plays an essential role in normal skeleton development, and genderrelated differences in skeletal tissue suggest that this phosphorylated glycoprotein may play an important role in the pathogenesis of several disorders (31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gamma carboxyglutamate, or Gla, is an amino acid residue with a high affinity for binding hydroxy-apatite. Gijsbers and co-workers have indicated that gamma-glutamate carboxylase activity is increased in normal arteries as compared to atherosclerotic vessels (30). In the normal vessel, therefore, Gla proteins may prevent the deposition of hydroxyapatite into the vessel wall (6); thus the in vivo and in vitro roles for the Gla proteins remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There exists, therefore, a number of proteins that chelate or sequester these ions (essentially calcium), thus lessening their availability and the possibility of precipitation (38,105). The use of mutated mouse models has revealed the existence of a number of inhibitors of calcification: matrix Gla proteins, osteopontin, pyrophosphate, ␤-glucosidase, carbonic anhydrase II, fetuin-A, desmin, osteoprotegerin (OPG), and Smad 6 (37).…”
Section: Balance Between Promoters and Inhibitors Of Calcificationmentioning
confidence: 99%